Gender and Citizenship under New Labour - Pascall, Gillian (Presses universitaires Blaise-Pascal, 2006)
Abstract To what extent has citizenship been transformed under the New Labour government to include women as equal citizens? This chapter will examine New Labour’s record in terms of alternative conceptions of citizenship: a model based on equal obligations to paid work, a model based on recognising care and gender difference, and a model of universal citizenship, underpinning equal expectations of care work and paid work with rights to the resources needed for individuals to combine both. It will argue that, while New Labour has signed up to the EU resolution on work-life balance, which includes commitment to a ‘new social contract on gender’, and has significantly increased resources for care, obligations to work are at the heart of New Labour ideas of citizenship, with work conceived as paid employment: policies in practice have done more to bring women into employment than men into care. Women’s citizenship is still undermined – though less than under earlier governments - by these unequal obligations and their consequences in social rights.